The influence of salmon surface mucus on the growth of Flavobacterium columnare - Staroscik, A. M.; Nelson, D. R. (Journal of Fish Diseases, 2008)
Flavobacterium columnare is the causative agent of columnaris disease. The presence of lesions on the gills, skin and fins of diseased fish suggests that F. columnare is able to utilize fish skin mucus as a substrate for growth and that exposure to this material would alter the expression of genes involved in the colonization of the outer surfaces of the fish. Growth, biofilm formation, extracellular protease production and changes in protein expression of F. columnare strain C#2 cultured in media supplemented with juvenile Atlantic salmon skin mucus were compared with the same media without mucus. C#2 was able to grow by using mucus as the sole nutrient source. Growth in mucus-containing media induced cells to grow as a biofilm and extracellular protease activity increased in mucus-containing cultures. SDS-PAGE protein profiles showed that expression of six extracellular proteins increased in mucus-containing media. These results demonstrate that salmon surface mucus promotes the growth of F. columnare and that exposure to mucus alters the growth characteristics of this bacterium with regard to protease production and biofilm formation. Further characterization of mucus-induced physiological changes will increase our understanding of the basis of virulence of this economically important fish pathogen. © 2008 The Authors.